KOHESI LEKSIKAL DALAM BERITA UTAMA HARIAN RIAU POS - Tambunan, Christina Hakim; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Cohesion is the relationship between the sentences in a discourse, both in strata certain grammatical and lexical strata. Sehubung with it, study here trying to describe the study of lexical cohesion in Riau Pos daily news. This research is a qualitative research. In this study, the authors use descriptive method. Descriptive method is a method performed by the following steps: collecting data, classify, analyze and make conclusions to get a picture of the object. The data source of this research is the daily headlines in Riau Pos listed starting from January 2 to January 31, 2015. Data collection techniques in this study is documentation techniques. Documentation techniques is to collect documents and data needed in the research problems studied intensively so as to support and add to the confidence and proof of an event. Writing collect data such as documents headline news in every issue of Riau Pos daily publication. The results of research there are five forms of lexical cohesion which will be described includes 18 synonyms, divided into four types, namely: inter-sentence synonym, inter-word, inter-phrase, and inter-morpheme, 6 antonyms, divided into four types, namely: antonym between words, between sentences, inter-phrase, and inter-morpheme, 5 underwriting meaning, 6 homonym, divided into four types, namely: homonymous between words, between sentences, inter-phrase, and inter-morpheme, and 5 hipernim , These results indicate the use of lexical cohesion in Riau Pos daily headlines.Keywords: Cohesion, lexical cohesion, Headlines, Riau Pos.